Analisis Komparasi Kecelakaan Lalu Lintas Di Jalan Tol Cikopo – Palimanan Sebelum dan Pada Saat Pandemi Covid-19 - Iqbal Maulana; Edi Purwanto; Alif Anggriat (Jurnal Penelitian Transportasi Darat, 2021)
ABSTRACTComparative Analysis of Traffic Accidents on Cikopo–Palimanan Toll Roads Before and During the Covid-19 Pandemic: Economic conditions, education and all aspects of Indonesian people's lives have been affected by the emergence of the Covid-19 pandemic so that the government implemented a Large-Scale Social Restriction (PSBB) policy at the beginning of 2020. From 2019 to July 2020, through data from the West Java POLDA Satlantas police and Astra Infra Toll Cipali PT Lintas Marga Sedaya as toll road operators, there were 1,075 traffic accidents on toll roads. The purpose of this study was to compare the level and fatality of accidents before and during the Covid-19 pandemic and to find out the differences in traffic accident-prone locations on toll roads before and during the Covid-19 pandemic. The research method used in this study is the variable rate of accidents, fatalities, traffic accident-prone locations using the HIRA (Hazard Identification Risk Assessment) analysis technique. The results of this study On Lane A of the Cikopo Palimanan Toll Road Before and During the Covid-19 Pandemic, there were 2 (two) similar accident-prone locations while the other 11 (eleven) prone locations were different. On Lane B of the Cikopo Palimanan Toll Road Before and During the Covid-19Pandemic, there was 1 (one) same accident-prone location while the other 14 (fourteen) prone locations were different. Results of the study, it can be concluded that there are differences in the parameters of accident-prone locations and the level of traffic accidents, while the fatality rate of traffic accidents is no difference between before the Covid-19 pandemic and during the Covid-19pandemic. Based on the Analysis (Hazard Identification Risk Assessment) road infrastructure Toll roads, the highest risk value for traffic accidents on the Cikopo – Palimanan toll road is on lane A STA 75+700, 82+100, 90+900, 100+700, 111+500, 114+300, 123+800, 151+ 300,153+500, 164+700 on lane B STA 74+100, 185+000.Keywords: Traffic Prone Location, Comparison, Before and During Covid-19ABSTRAKKondisi perekonomian, pendidikan dan segala aspek kehidupan masyarakat Indonesia terdampak oleh munculnya pandemi Covid-19 sehingga pemerintah menerapkan kebijakan Pembatasan Sosial Berskala Besar (PSBB) di awal tahun 2020. Pada tahun 2019 hingga Juli 2020 melalui data kepolisian Satlantas POLDA Jawa Barat dan Astra Infra Tol Cipali PT Lintas Marga Sedaya selaku operator jalan tol terdapat 1.075 Kejadian Kecelakaan lalu lintas di jalan tol. Tujuan dari penelitian ini adalah membandingkan tingkat dan fatalitas kecelakaan sebelum dan pada saat pandemi Covid-19 serta Mengetahui perbedaan lokasi rawan kecelakaan lalu lintas di ruas jalan tol sebelum dan pada saat pandemi Covid-19. Metode penelitian yang digunakan dalam penelitian ini adalah variabel tingkat kecelakaan, fatalitas, lokasi rawan kecelakaan lalu lintas menggunakan tekniki analisis HIRA (Hazard Identification Risk Assesment). Hasil penelitian ini Pada Jalur A Tol Cikopo Palimanan Sebelum dan Saat Pandemi Covid-19ada 2 (dua) lokasi rawan kecelakaan yang sama sedangkan 11 (sebelas) lokasi rawan yang lainnya berbeda. Pada Jalur B Tol Cikopo Palimanan Sebelum dan Saat Pandemi Covid-19ada 1 (satu) lokasi rawan kecelakaan yang sama sedangkan 14 (empat belas) lokasi rawan yang lainnya berbeda. Dari hasil penelitian dapat disimpulkan bahwa ada perbedaan pada parameter lokasi rawan kecelakaan dan tingkat kecelakaan lalu lintas, sedangkan tingkat fatalitas kecelakaan lalu lintas tidak ada perbedaan antara sebelum pandemi Covid-19 dan pada saat pandemi covid 19. Berdasarkan Analisis (Hazard Identification Risk Assesment) infrastruktur jalan tol diperoleh Nilai Risiko terjadinya kecelakaan lalu lintas di jalan tol Cikopo – Palimanan tertinggi yaitu pada jalur A STA 75+700, 82+100, 90+900, 100+700, 111+500, 114+300, 123+800, 151+300,153+500, 164+700 pada jalur B STA 74+100, 185+000.Kata kunci: Lokasi Rawan, Komparasi, Sebelum dan Saat Covid-19